Parametrisation for boundary value problems with transcendental non-linearities using polynomial interpolation - Rontó András (Electronic journal of qualitative theory of differential equations, 2018)
A constructive technique of analysis involving parametrisation and polynomial interpolation is suggested for general non-local problems for ordinary differential systems with locally Lipschitzian transcendental non-linearities. The practical application of the approach is shown on a numerical example.